2014
DOI: 10.4103/0019-5545.124714
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing access to psychiatric treatment in persons with schizophrenia: A qualitative study in a rural community

Abstract: Purpose:In low and middle-income countries, about 80% of those who need mental health services do not receive them. Reasons for this have not been systematically studied. In this qualitative study, we explored this issue in a rural community of South India among schizophrenia patients.Materials and Methods:Patients who had never sought psychiatric treatment despite long-standing psychotic illnesses were identified as part of a community intervention program. In-depth interviews were conducted with patients’ ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…This does not only influence the choice of initial help sought but the stigma that follows might cause families to conceal the matter and delay help-seeking. Previous studies done in other countries have consistent results with this study (21,(42)(43)(44). Hence, addressing these cultural issues while developing intervention for promoting professional helpseeking behavior is important.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This does not only influence the choice of initial help sought but the stigma that follows might cause families to conceal the matter and delay help-seeking. Previous studies done in other countries have consistent results with this study (21,(42)(43)(44). Hence, addressing these cultural issues while developing intervention for promoting professional helpseeking behavior is important.…”
Section: Discussionsupporting
confidence: 89%
“…Many caregivers normalized such subtle changes which eventually delayed professional helpseeking. These findings are not surprising and have been described in other studies (15,16,21). In a qualitative study looking at how people identify and respond to emerging psychosis, Judge et al (16) found themes like normalization, giving explanation, withdrawal, avoiding help and coming to terms with psychosis which posed as barriers to help-seeking (16).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Hence they tend to ignore the patient’s symptoms and treatment a practice which results into relapse [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Spirituality can potentially help patients in the process of illness recovery, by facilitating their autonomy and assisting them to live and grow beyond the limitations imposed by their illness . Faith, culture, spirituality, family, and community can all play a role in influencing access to, and provision of, psychiatric treatment of people with SMI (Reddy et al, 2014).…”
Section: Theme: Religion Spirituality Culture and Traditional Pramentioning
confidence: 99%